ESTIMATION GENE EFFECTS BASED ON JOINT SCALING TEST AND SOME GENETIC PARAMETERS IN FOUR MAIZE CROSSES 1-YIELD COMPONENTS - H. Hadi, B. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The objective of this study to estimate the components of genetic variation, phenotypic (PCV) ,genotypic(GCV) coefficient of variation, genetic gain and its percentage. An experiment was conducted at the field of Field Crop Dept.Coll. Agric.-Univ. Baghdad, using four crosses (FI01301 Rustico), (AntignaoHi39× Nostred), (Lo1391× Rustico) and (Rusticocangini× Rustico) which developed from crossing of genetically different of six inbred lines for maize (Zae mays L.), introduced from Italy. Genetic parameters were estimated according to the Joint scaling test using the randomized complete block design with four replications. The components of genetic variance; Additive and dominance of the maize grain yield and some trait, were estimated. The results showed that the values of Chi square were significant for all the studied some traits of all crosses, thus the simple additive – dominance model in four crosses exhibited lack of good fit for all traits, indicates the role of non-allelic interaction. Dominance gene action was higher than additive for most traits. Therefore the hybridization would be more effective than population selection to improve these traits for these crosses.